Comparison of changes in creatinine values in heart failure patients pre and post angiography in the reduced with preserved ejection fraction group - Liling, Fransiska Rosdiana; Mappangara, Idar; Rasyid, Haerani; Bakri, Syakib; Aman, Andi Makbul; Zainuddin, Andi Alfian (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Sudden changes in renal function are a common complication of coronary angiography, and percutaneous coronary intervention, especially due to contrast-induced acute kidney injury or contrast-induced nephropathy. Iodine contrast media is essential in invasive and interventional cardiac procedures. Increased use of contrast media, and an increasing number of invasive cardiac procedures performed on high-risk patients. This study aims to determine the comparison of changes in creatinine values of pre- and post-angiography patients in the HFrEF and HFpEF groups. Methods: Retrospective cohort with 85 samples of Heart Failure patients with HFrEF and HFpEF who underwent angiography. The data collection method uses secondary data, namely medical record data at the Integrated Heart Center of RSUP Dr. Wahidin Sudirohusodo. Statistical analysis used the Wilcoxon Signed Ranks Test and Mann-Whitney. Statistical test results are considered significant if the test p value is <0.05. Results: Comparison of pre and post angiography creatinine values in all study samples. There was a significant difference in mean creatinine values, namely post angiography, 1.06 + 0.45 mg/dL compared to pre angiography, namely 1.00 + 0.40 mg/dL (p<0.05). HFrEF patients were found to have significantly higher creatinine values post angiography, 0.91+0.27 mg/dL (p<0.05). There were no significant results for pre-angiography creatinine values in HFrEF and HFpEF patients and post-angiography in HFrEF and HFpEF patients (0.062). Conclusion: HFrEF patients who underwent angiography experienced an increase in creatinine values after angiography.